Fatty Acid Composition of the Seed Pods of Albizia lebbeck and the Leaves of Samanea saman - Ali, Md Ramjan; Chhanda, Sadia Afrin; Muslim, Tanvir; Rahman, Md Azizur (Dhaka University Journal of Science, 2016)
Abstract not available Dhaka Univ. J. Sci. 64(2): 179-180, 2016 (July)